2011
DOI: 10.1111/j.1744-7917.2011.01461.x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed development of the whitefly (Bemisia tabaci) and increased parasitism by Encarsia bimaculata in response to sublethal doses of piperonyl butoxide

Abstract: Effects of sublethal piperonyl butoxide (PB) on parasitization of Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) by Encarsia bimaculata Heraty et Polaszek (Hymenoptera: Aphelinidae) were evaluated both in cage and greenhouse experiments. When first, second and third instar B. tabaci nymphs were treated with PB, all but the first instar were significantly prolonged. Data indicated that sublethal PB could improve E. bimaculata parasitism rates without influencing parasitoid eclosion rates. Prolonged develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
(43 reference statements)
1
6
0
Order By: Relevance
“…For DT 80 , an even greater delay in development was observed, ranging from 6.8 to 16 days, again depending on the insecticide exposure method. It is expected that delays in nymph development demonstrated in this study could affect whitefly population growth and parasitism levels in planta , in ways similar to those reported in previous studies …”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…For DT 80 , an even greater delay in development was observed, ranging from 6.8 to 16 days, again depending on the insecticide exposure method. It is expected that delays in nymph development demonstrated in this study could affect whitefly population growth and parasitism levels in planta , in ways similar to those reported in previous studies …”
Section: Discussionsupporting
confidence: 86%
“…Chemically induced effects on whitefly development can slow the pest growth rate, as well as enhance the level of control by beneficials. It has been demonstrated that the parasitoids Encarsia bimaculata and Eretmocerus mundus (Hymenoptera: Aphelinidae) exploit the prolonged presence of appropriate B. tabaci nymphal stages after PB exposure, increasing parasitism levels . According to Qian et al , after exposure to sublethal doses of PB, the mean development time increased by 2.5–4.5 days, depending on the dose and the nymphal stage exposed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological control: biopesticides, a mass-produced agent manufactured from a living microorganism or a natural product, may offer a solution to disease control through introduction of predators and parasitoids of the vector. Biopesticides based on microbials such as Beauveria bassiana (effective on nymphs and adults) or Paecilomyces fumosoroseus, Green lacewings, ladybirds, minute pirate bugs, big-eyed bugs, and damsel bugs and Encarsia bimaculata [21] based on microbials such as Beauveria bassiana (effective on nymphs and adults) or Paecilomyces fumosoroseus. Green lacewings, ladybirds, minute pirate bugs, bigeyed bugs, damsel bugs and the parasitoid, Encarsia bimaculata [21].…”
Section: Begomovirus Species and Its Genome Organizationmentioning
confidence: 99%
“…Biopesticides based on microbials such as Beauveria bassiana (effective on nymphs and adults) or Paecilomyces fumosoroseus, Green lacewings, ladybirds, minute pirate bugs, big-eyed bugs, and damsel bugs and Encarsia bimaculata [21] based on microbials such as Beauveria bassiana (effective on nymphs and adults) or Paecilomyces fumosoroseus. Green lacewings, ladybirds, minute pirate bugs, bigeyed bugs, damsel bugs and the parasitoid, Encarsia bimaculata [21]. Encarsia formosa is one of the most efficient and studied bioagents of B. tabaci.…”
Section: Begomovirus Species and Its Genome Organizationmentioning
confidence: 99%